Energetska varnost in trajnosten energetski sistem: izbrani vidiki v kontekstu evropske energetske unije - Ferčič, Aleš (Podjetje in delo, 2022)
The article discusses energy security based on sustainable energy system in the context of the energy union. The focus is on the question whether the post-Lisbon primary legal framework appropriately treats energy, since the latter is not a classical market good. In this regard, the author finds that this is not the case and he opposes thinking of energy as being merely the fifth economic freedom within the internal market. The author proposes changes of the existing primary legal framework in order to ensure appropriate treatment of energy, with an emphasis on energy security based on a sustainable energy system.
Keywords: energetska unija; energetska varnost; energija; energy; energy security; energy union; internal market; notranji trg; protection of environment; sustainable energy system; trajnosten energetski sistem; varstvo okolja